Social-Cultural Factors which Influence Local Politics in Si Sa Ket - Wongkamjan, Akapong (Journal of Human and Society, Sisaket Rajabhat University, 2023)
This research aims to study the relationship between social, cultural, political, and local politics in Si Sa Ket. The sample groups consist of 200 men and 200 women who have the right to vote and have been living in various districts of Si Sa Ket Province. The author applied Quota Sampling to select the population for the research and used questionnaires as the research tool. The results showed that the majority of the research population was over 45 years old (200 people - 50%), had completed compulsory education (175 people - 43.75%), were engaged in farming (40 people - 35%), and had local citizenship status by being born in the constituency area (280 people - 70%) The sample groups expressed their opinions on various social-cultural factors that influence local politics. The top three issues rated highest were the importance of candidates (mean score - 4.53), the relationship between the local community and kinship (mean score - 4.52), and the significance of local political groups (mean score - 4.51). The medium-level issue was the importance of the national network of politicians (mean score - 3.45). After analyzing the relationship between social-cultural factors and their influence on local politics in Si Sa Ket, the author found that these factors significantly influenced local politics at a significance level of 0.05, confirming the research hypothesis. Upon closer examination of each issue, the author found that personal importance, the significance of local political groups, emphasis on vision/policy guidelines, presentation of the policy vision, and the use of local kinship relations all showed a positive relationship with local elections at a significance level of 0.05. However, the importance of the national network of politicians did not show a significant relationship with local election factors.